Extracellular vesicles protein cargo as targets for Alzheimer’s disease - Pinho, Beatriz Almeida (2024)
Alzheimer’s Disease (AD) is a complex neurodegenerative disorder characterized by cognitive progressive decline, and the leading cause of dementia worldwide. The diagnosis of AD is challenging, and so far, there are no molecular tools based on peripheral biofluids available. Blood-derived extracellular vesicles (EVs) may constitute an accessible and non-invasive resource of biomarkers for AD. This project aimed to identify new biomarker candidates in EVs with diagnostic potential for AD from an antibody microarray analysis, which comprises pan- and phospho-specific antibodies. To identify EVs-enriched proteins which may constitute targets for AD 2 approaches were followed: i) an overlap with a list of genes related with AD from DisGeNET and ii) an overlap with a list of proteins also obtained by microarray analysis from AD cases. Further, protein-protein interaction networks were constructed, and the selected proteins/phosphoproteins, namely CTNNB1, RELA, PKM, GSK3α, MFN2, STAT1, and RAF1 tested in an AD-mimicking cell model. Alterations were observed in the levels of some targets tested, linked to AD pathological events, such as amyloid precursor protein (APP) processing, tau phosphorylation, neuroinflammation and synaptic dysfunction. Taken together, this thesis showed the potential of microarray analysis as an effective method for identifying AD-related targets. Further, the candidates identified are enriched in EVs and involved in several key pathogenic events, supporting their relevance as putative targets for AD diagnosis or therapeutics.